Biokonversi Kertas HVS Bekas Menjadi Bioetanol Dengan Variabel Konsentrasi Saccharomyces cerevisiae - Sisi Oktadira Kalpatari; Chairul Chairul; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
One effort to overcome the scarcity of oil fuels is by finding alternative fuels from renewable natural resources. Biomass waste is one of the energy sources in the form of lignocellulose which can produce bioethanol. Indirectly, used Hvs paper is cellulose which has a lot of waste. The level of consumption of Hvs paper in Indonesia and in the world continues to increase. The consequence of increasing consumption of Hvs paper has a high impact on the waste paper produced. The large amount of paper waste available provides an opportunity for efforts to utilize the paper waste. The utalization of used Hvs paper is usually only recycled into Hvs paper again, but the quality is not as good as initially. This study is aimed to convert used Hvs paper become bioethanol because used Hvs paper still contains cellulose as its main raw material. In this study, The process of making bioethanol from used Hvs paper has done with the pretreatment, hydrolysis and fermentation stages. The pretreatment process uses NaOH, then the hydrolysis process with dilute acid is used 1.5 M, hydrolysis temperature of 1300C, time of 120 minutes, The last process is fermentation. The fermentation process was carried out by varying the concentration of yeast which is 1 gr, 3 gr, 5 gr and fermentation time which is 48 hours, 96 hours, 144 hours, and 192 hours. In acid hydrolysis, the maximum sugar concentration was produced at 131.23 gr / L. The best concentration of yeast in this study was 5 grams at the best fermentation time of 144 hours with bioethanol levels obtained at 6% or 47.36 g / L.Keywords: bioethanol, fermentation, hydrolysis, Saccharomyces cerevisiae, Hvs paper